Poly(methyl methacrylate) blends with quaternized polyethyleneimine: A study of morphology, optical, thermal and mechanical properties - Rafael Affonso Netto; Guilherme Ribeiro de Carvalho; Lucas Henrique Staffa; Liliane Maria Ferrareso Lona (eXPRESS Polymer Letters)
This study aimed first to promote the alkylation of polyethyleneimine (PEI), developing its alkylated (quaternary) form (QA-PEI) by inserting alkyl groups into amine groups. Subsequently, polymer blends with poly(methyl methacrylate) (PMMA) were prepared via solvent casting, and finally, the physicochemical, optical, and mechanical behavior of the resulting PMMA/QA-PEI were assessed. Elemental analyses, Fourier-transform infrared spectroscopy (FT-IR), and hydrogen nuclear magnetic resonance spectroscopy (1H-NMR) confirmed that the PEI alkylation successfully converted the amine groups into quaternary ammonium groups. When added to PMMA, QA-PEI altered its coloration, making it yellow. In addition, higher contents of QA-PEI hindered PMMA transmittance and increased its opacity due to the larger QA-PEI domains. Scanning electron microscopy (SEM) images showed that PMMA and QA-PEI formed a phase-separated system, establishing a droplet-matrix morphology. The thermal and mechanical behavior showed some compatibility between PMMA and QA-PEI as thermal resistance slightly improved and PMMA glass transition temperature (Tg) decreased. The tensile strength was also improved in the PMMA/QA-PEI blends without significant change in strain at break and tensile modulus.